2014
DOI: 10.1155/2014/383482
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Repeatedly Preadministered Brazilian Propolis Ethanol Extract against Stress‐Induced Gastric Mucosal Lesions in Rats

Abstract: The present study was conducted to clarify the protective effect of Brazilian propolis ethanol extract (BPEE) against stress-induced gastric mucosal lesions in rats. The protective effect of BPEE against gastric mucosal lesions in male Wistar rats exposed to water-immersion restraint stress (WIRS) for 6 h was compared between its repeated preadministration (50 mg/kg/day, 7 days) and its single preadministration (50 mg/kg). The repeated BPEE preadministration attenuated WIRS-induced gastric mucosal lesions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…Thus, the protective effect of BPEE against WIRS‐induced liver cell damage was found to be diminished at a high dose. In previous reports (Ohta et al , ; Nakamura et al , ) we have confirmed that BPEE (10 or 50 mg/kg) and VE (250 mg/kg) preadministered to rats with 6 h of WIRS have no effect on stress responses, whereas BPEE (100 mg/kg) preadministered to the stressed rats enhances stress responses. In addition, we have suggested that orally administered BPEE could exert a less protective effect against gastric mucosal lesions in rats with 6 h of WIRS at a dose of 100 mg/kg than at a dose of 50 mg/kg by enhancing the sensitivity of stress responses (Nakamura et al , ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, the protective effect of BPEE against WIRS‐induced liver cell damage was found to be diminished at a high dose. In previous reports (Ohta et al , ; Nakamura et al , ) we have confirmed that BPEE (10 or 50 mg/kg) and VE (250 mg/kg) preadministered to rats with 6 h of WIRS have no effect on stress responses, whereas BPEE (100 mg/kg) preadministered to the stressed rats enhances stress responses. In addition, we have suggested that orally administered BPEE could exert a less protective effect against gastric mucosal lesions in rats with 6 h of WIRS at a dose of 100 mg/kg than at a dose of 50 mg/kg by enhancing the sensitivity of stress responses (Nakamura et al , ).…”
Section: Discussionsupporting
confidence: 84%
“…In previous reports (Ohta et al , ; Nakamura et al , ) we have confirmed that BPEE (10 or 50 mg/kg) and VE (250 mg/kg) preadministered to rats with 6 h of WIRS have no effect on stress responses, whereas BPEE (100 mg/kg) preadministered to the stressed rats enhances stress responses. In addition, we have suggested that orally administered BPEE could exert a less protective effect against gastric mucosal lesions in rats with 6 h of WIRS at a dose of 100 mg/kg than at a dose of 50 mg/kg by enhancing the sensitivity of stress responses (Nakamura et al , ). Therefore, it is suggested that BPEE preadministered at a dose of 100 mg/kg could diminish the protective effect of BPEE against liver cell damage in rats with 6 h of WIRS by enhancing the sensitivity of stress responses.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The method earlier reported by Nakamura, Ohta, Ikeno, Ohashi, and Ikeno () was followed to prepare the rat liver homogenate that was used as the source of XO in this study. Briefly, 3 Wistar rats, weighing 200–220 g, were mildly anesthetized with ether, and sacrificed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it acts as an antioxidant drug by decreasing the extent of lipid peroxidation (LPO) and increasing the activities of enzymatic antioxidants [52] . Moreover, it is a powerful ROS scavenger [53] as it enhances the levels of reduced glutathione (GSH) suggesting GSHdependent detoxification of free radicals [54] . Propolis also inhibits the migration of neutrophil thus reduces the inflammatory response [55] .…”
Section: Discussionmentioning
confidence: 99%